Efficacy and Safety of Angiotensin-Converting Enzyme Inhibitor in Combination with Angiotensin-Receptor Blocker in Chronic Kidney Disease Based on Dose: A Systematic Review and Meta-Analysis - Zhao, Mingming; Wang, Rumeng; Yu, Yi; Chang, Meiying; Ma, Sijia; Zhang, Hanwen; Qu, Hua; Zhang, Yu (Frontiers in Pharmacology, 2021)
Background: The purpose of this meta-analysis was to evaluate the controversy of angiotensin-converting enzyme inhibitor (ACEI) in combination with angiotensin-receptor blocker (ARB) in the treatment of chronic kidney disease (CKD) based on dose. Methods: PubMed, EMBASE, and Cochrane Library were searched to identify randomized controlled trials (RCTs) from inception to March 2020. Random effects model was used to calculate the effect sizes. Potential sources of heterogeneity were detected using sensitivity analysis and meta-regression. Results: This meta-analysis of 53 RCTs with 6,375 patients demonstrated that in patients with CKD, ACEI in combination with ARB was superior to low-dose ACEI or ARB in reducing urine albumin excretion (SMD, -0.43; 95% CI, -0.67 to -0.19; P=0.001), urine protein excretion (SMD, -0.22; 95% CI, -0.33 to -0.11; P<0.001), and blood pressure (BP), including systolic BP (WMD, -2.89; 95% CI, -3.88 to -1.89; P<0.001) and diastolic BP (WMD, -3.02; 95% CI, -4.46 to -1.58; P<0.001). However, it was associated with decreased glomerular filtration rate (GFR) (SMD, -0.13; 95% CI, -0.24 to -0.02; P=0.02) and increased rates of hyperkalemia (RR, 2.07; 95% CI, 1.55 to 2.76; P<0.001) and hypotension (RR, 2.19; 95% CI, 1.35 to 3.54; P=0.001). ACEI in combination with ARB was more effective than high-dose ACEI or ARB in reducing urine albumin excretion (SMD, -0.84; 95% CI, -1.26 to -0.43; P<0.001) and urine protein excretion (SMD, -0.24; 95% CI, -0.39 to -0.09; P=0.002), without decrease in GFR (SMD, 0.02; 95% CI, -0.12 to 0.15; P=0.78) and increase in rate of hyperkalemia (RR, 0.94; 95% CI, 0.65 to 1.37; P=0.76). Nonetheless, the combination did not decrease the BP and increased the rate of hypotension (RR, 3.95; 95% CI, 1.13 to 13.84; P=0.03) compared with high-dose ACEI or ARB. Conclusions: ACEI in combination with ARB is superior in reducing urine albumin excretion and urine protein excretion. The combination is more effective than high-dose ACEI or ARB without decreasing GFR and increasing the incidence of hyperkalemia. Despite the risk of hypotension, ACEI in combination with ARB is a better choice for CKD patients who need to increase the dose of ACEI or ARB (PROSPERO CRD42020179398).